Quantitative analysis of clot density, fibrin fiber radius, and protofibril packing in acute phase myocardial infarction. Issue 205 (September 2021) - Siniarski, Aleksander; Baker, Stephen R.; Duval, Cédric; Malinowski, Krzysztof P.; Gajos, Grzegorz; Nessler, Jadwiga; Ariëns, Robert A.S.
Abstract: Introduction: Coronary artery disease is associated with impaired clot structure. The aim of this study was to investigate acute phase myocardial infarction (AMI) and provide detailed quantitative analysis of clot ultrastructure. Materials and methods: Clot formation and breakdown, pore size, fiber density, fiber radius and protofibril packing were investigated in plasma clots from AMI patients. These data were compared to those from healthy controls. Results: Analysis on clot formation using turbidity showed increased lag time, suggesting changes in protofibril packing and increased fiber size for AMI patients compared to healthy controls. Additionally, increased average rate of clotting and decreased time to maximum absorbance in AMI patients suggest that clots formed more quickly. Moreover, we observed increased time from max OD to max rate of lysis. Increased fibrinogen and decreased plasminogen in AMI patients were accounted for in represented significant differences. AMI samples showed increased time to 25% and 50% lysis, but no change in 75% lysis, representative of delayed lysis onset, but expediated lysis once initiated. These data suggest that AMI patients formed less porous clots made from more densely packed fibers with decreased numbers of protofibrils, which was confirmed using decreased permeation and increased fiber density, and decreased turbidimetry. Conclusions: AMI plasma formed clots that were denser, less permeable, and lysed more slowly than healthy controls. These findings were confirmed by detailed analysis of clot ultrastructure, fiber size, and protofibril packing. Dense clot structures that are resistant to lysis may contribute to a prothrombotic milieu in AMI.